Pengaruh CSR Terhadap Nilai Perusahaan Dengan Good Corporate Governance Dan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Firmansyah, Didi; Surasni, Ni Ketut; Pancawati, Sri (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p12, 2020)
The main objective of the company is to increase the value of the company through increasing the prosperity of the owner or shareholders. When the stock price rises, it means the value of the company increases and the welfare of the owner increases. Therefore companies that have gone public will strive to increase the prosperity of their owners or shareholders in order to increase the value of the company. The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) on corporate value with Good Corporate Governance (GCG) and company size as a moderating factor. The study population was 171 companies with a sample of 110 companies. Data analysis techniques using MRA (moderated regression analysis). Statistical results show that CSR influences firm value, GCG can moderate the influence of CSR on firm value, and so does company size can moderate the effect of CSR on firm value. Keywords: Corporate Social Responsibility (CSR); Good Corporate Governance (GCG); company size; the value of the company